Primary Care For Nephrologists: revisiting some new concepts. - Omer Sabir (Pakistan Journal of Kidney Diseases, 2021)
IRIS was reported initially during the treatment of Human immunodeficiency virus with antiretroviral therapy (ART). It was noted that there was an increase in the paradoxical infectious process such as tuberculosis with improvement of the immune system. Most of the cases have been reported with mycobacterium tuberculosis (TB), however other organisms have been implicated also. Similar episodes were also noted in non-HIV patients undergoing treatment for TB, though milder and self-limiting. In patients responding to ART, almost 30% develop IRIS.